Himar1 Transposon for Efficient Random Mutagenesis in Aggregatibacter actinomycetemcomitans - Ding, Qinfeng; Tan, Kai Soo (Frontiers in Microbiology, 2017)
Aggregatibacter actinomycetemcomitans is the primary etiological agent of aggressive periodontal disease. Identification of novel virulence factors at the genome-wide level is hindered by lack of efficient genetic tools to perform mutagenesis in this organism. The Himar1 mariner transposon is known to yield a random distribution of insertions in an organism’s genome with requirement for only a TA dinucleotide target and is independent of host-specific factors. However, the utility of this system in A. actinomycetemcomitans is unknown. In this study, we found that Himar1 transposon mutagenesis occurs at a high frequency (×10-4), and can be universally applied to wild-type A. actinomycetemcomitans strains of serotypes a, b and c. The Himar1 transposon inserts were stably inherited in A. actinomycetemcomitans transconjugants in the absence of antibiotics. A library of 16,000 mutant colonies of A. actinomycetemcomitans was screened for reduced biofilm formation. Mutants with transposon inserts in genes encoding pilus, putative ion transporters, multidrug resistant proteins, transcription regulators and enzymes involved in the synthesis of extracellular polymeric substance, bacterial metabolism and stress response were discovered in this screen. Our results demonstrated the utility of the Himar1 mutagenesis system as a novel genetic tool for functional genomic analysis in A. actinomycetemcomitans.